Differential thermal analysis of Kharidhunga magnesite - Dangol, Vishnu (Journal of Nepal Geological Society, 1991)
The DTA curves of seven representative samples from the Kharidhunga Magnesite Deposit arc asymmetric and show a sharp rise after attaining the maxima between 670 and 700 oC, which indicates the siliceous nature of the magnesite. The overlapped endothermic peaks al 770 oC and 860 oC characterize the presence of calcite and dolomite respectively as the other impurities. The results of DTA and TG are also compared with the available data of chemical analysis.